Growth and development of tomato (Lycopersicon esculentum mill.) cultivars in vitro under salinity condition - Ahmed Mohamed, Abdalmajid Nasher (2012)
The salinity of soil and irrigation water present one of the greatest environmental strains affecting plant growth and development. Salinity influences agricultural production in most parts on the world. The tissue culture technique provides a unique chance for studying many aspects of plant growth and development, and studying the physiological and biochemical processes under controlled environment, which contribute to salinity tolerance. In addition, it offers greater control than in vivo growth conditions and has the benefit of small scale with clear visibility for observation of shoot and root responses in the presence of enforced stress. This study was carried out in the Agrobiotechnology laboratory- Faculty of Agriculture and plant physiology in ITA-MTDC, UPM, and achieved the following objectives: Establishment of a protocol for shoot regeneration from hypocotyl and cotyledon explants by different concentrations of BAP hormone, response hypocotyl and cotyledon explants to shoot formation under NaCl concentration, study of the changes in organic and inorganic solutes in shoots grown from hypocotyl, and cotyledon explants under NaCl stress and increase for NaCl tolerance by shoot apices sub-culture under different levels of NaCl stress. In vitro, response of hypocotyl and cotyledon explants to shoots regeneration in MS medium supplemented different levels of 6-benzylaminopurine (0. 1,2, 4) mg/l was studied. The cultures harvested after six weeks from culture explants. Different responses were recorded in tomato explants under different levels of BAP. The formation of roots from hypocotyl explants found in the control treatment, whereas the cotyledons did not show any response. The media supplemented with 4 mg/l BAP resulted in callus in both explants. The medium supplemented 2 mg/l BAP was most effective for the induction of adventitious shoots for both the hypocotyl, and cotyledon explants in tomato cultivars; where the number of shoots/explant was 4 and 4.5 in hypocotyls and cotyledons Pearl cultivar and 2.25 and 3 shoots/explants in hypocotyls and cotyledons Beril cultivars respectively. The best shoots length achieved by hypocotyl explants in Pearl cultivar; where it was 1.62 cm in medium was supplemented 2 mg/l BAP. In vitro, evaluations of sodium chloride (NaCl) effects on two tomato cultivars (Pearl and Beril) were investigated with four NaCl levels (0, 25, 50 and 75 mM) using hypocotyl and cotyledon explants. The explants were cultured in MS media having 2.0 mg/l BAP (the suitable medium from the previous experiment) along with different concentrations of NaCl. The cultures harvested after eight weeks from culture explants. The growth characteristics (shoots number, shoots length, fresh weight and dry weight)decreased with increasing NaCl in the growth medium. The reduction percentage in shoots length was 85% in high level NaCl (75 mM) in comparison with control; whereas the reduction in shoots number, fresh weight and dry weight was 65, 64 and 54% in high level NaCl. In addition,there was greater degradation of chlorophyll b than chlorophyll a and different responses of tomato cultivars and explants for salt tolerance in vitro;where the reduction percentage in chlorophyll a and b was 69%, 76% in high level NaCl. The growth characteristics and chlorophyll content were superior in the Beril compared to the Pearl cultivar, and the shoots induced from cotyledon explants showed best in growth characteristics and chlorophyll content than the shoots induced from hypocotyl explants under NaCl stress. The findings may contribute to best multiplication from cotyledon explants in Beril cultivar to raise a salt-tolerant line for future use.